The response of reproducing Japanese quail to dietary valine - Martinez, K. N.M. [UNESP]; Viana, G. da S.; Silva, E. P. da [UNESP]; Reis, M. P. [UNESP]; Gous, R. M.; Sakomura, N. K. [UNESP] (Taylor & Francis, 2021)
1. A feeding trial was conducted to measure the responses of Japanese quail to dietary valine. In total, 280 Japanese quail were randomly assigned to eight treatments giving seven replicates (cage–35 cm length, 35 cm width × 15 cm high). Experimental diets were formulated using a dilution technique to give a range dietary Val concentration (1.97 to 9.85 g/kg). 2. Feed intake was maximised at 6.66 g Val/kg and above, but declined linearly below this level. Body weight reached a maximum of 170 g on 6.66 g Val/kg. Egg output peaked at 9.5 ± 0.3 g/bird/d with an egg weight of 11 g for the 6.66 g Val/kg diet. Rate of laying for the group that received the feed with the lowest Val content was close to zero (1.40%), but egg weight on this treatment was 70% of the maximum egg weight. Valine required per gram of egg output was estimated as 10.6 mg/g, whereas the maintenance requirement was 159 mg/kg body weight. Val required for maximum egg output was estimated in 154 mg/d. 3. The marginal cost of Val in Brazil currently is negative below a level of 8.0 g/kg feed, which is above that required for maximum egg output. Consequently, Val cannot be regarded as a limiting amino acid currently, as the optimum economic intake exceeds the requirements of all the individuals in the population. The price of a quail egg weighing 11 g in Brazil at the time of the experiment was R$ 0.021. Even if the marginal revenue for these eggs was doubled to 0.4 c/g, there would be no reason to increase the intake of Val.
Keywords: Amino acids; dilution technique; egg production; marginal cost; marginal revenue